Tissue Factor Reduction and Tissue Factor Pathway Inhibitor Release after Heparin Administration - Gori, A. M.; Pepe, G.; Attanasio, M.; Falciani, M.; Abbate, R.; Prisco, D.; Fedi, S.; Giusti, B.; Brunelli, T.; Comeglio, P.; Gensini, G. F.; Neri Serneri, G. G. (Thrombosis and Haemostasis, 1999)
Elevated plasma levels of tissue factor (TF) and tissue factor pathway inhibitor (TFPI) and large amounts of monocyte procoagulant activity (PCA) have been documented in unstable angina (UA) patients. In in vitro experiments heparin is able to blunt monocyte TF production by inhibiting TF and cytokine gene expression by stimulated cells and after in vivo administration it reduces adverse ischemic outcomes in UA patients. TF and TFPI plasma levels and monocyte PCA have been investigated in 28 refractory UA patients before and during anticoagulant subcutaneous heparin administration (thrice daily weight- and PTT-adjusted for 3 days) followed by 5000 IU × 3 for 5 days. After 2-day treatment, immediately prior to the heparin injection, TF and TFPI plasma levels [(median and range): 239 pg/ml, 130-385 pg/ ml and 120 ng/ml, 80-287 ng/ml] were lower in comparison to baseline samples (254.5 pg/ml, 134.6-380 pg/ml and 135.5 ng/ml, 74-306 ng/ml). Four h after the heparin injection TF furtherly decreased (176.5 pg/ml, 87.5-321 pg/ml; -32.5%, p<0.001) and TFPI increased (240.5 ng/ml, 140-450 ng/ml; +67%, p<0.0001).After 7-day treatment, before the injection of heparin, TF and TFPI plasma levels (200 pg/ml, 128-325 pg/ml and 115 ng/ml, 70-252 ng/ml) significantly decreased (p<0.05) in comparison to the pre-treatment values. On the morning of the 8th day, 4 h after the injection of heparin TF plasma levels and monocytes PCA significantly decreased (156.5 pg/ml, 74-259 pg/ml and from 180 U/105 monocytes, 109-582 U/105 monocytes to 86.1 U/105 monocytes, 28-320 U/105 monocytes; - 38% and -55% respectively) and TFPI increased (235.6 ng/ml, 152-423 ng/ ml; +70%, p<0.001). In conclusion, heparin treatment is associated with a decrease of high TF plasma levels and monocyte procoagulant activity in UA patients. These actions of heparin may play a role in determining the antithrombotic and antiinflammatory properties of this drug.